Анатомия и макро-микроморфология нервов надкостницы таза лошади - Павловский, Ю.А. (Вестник зоологии, 1969)
The investigation carried out by the author showed that pelvic bones in horse are innervated by the nerves of lumbo sacral plexus and branches of truncus sympathicus. The dorsal part of pelvic girdle — ilium — is innervated by the dorsal branches of the V and VI lumbar nerves, by iliohypogastric, ilio-inguinal, femoral, cranial glutaeal and sciatic nerves. The ventral part — pubic bone and ischium is innervated by femoral, obturator, caudal glutaeal and sciatic nerves. Non-uniformity of innervation of different parts of pelvis is also reflected in macromicroscopic picture of the bone periosteum nerves. The periosteum of ilium contains a greater number of nervous elements than that of pubic bone and ischium. The data obtained confirmed the general principles of the bone innervation that were established by other investigators.